2021
DOI: 10.3390/ijerph18041763
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Prediabetes and Type 2 Diabetes Mellitus in Football Players: A Novel Multi Football Clubs Cross Sectional Study

Abstract: Sports offer great benefits, improving health and reducing the risk of illnesses. This study’s aim was to investigate the prevalence of prediabetes and type 2 diabetes mellitus in football players compared to population based non-elite athlete control subjects. Initially 1100 male volunteers, (550) football players, and (550) population based non-elite athlete control subjects were interviewed. After socio-demographic and medical history analysis, 756 (378) nonsmoker male football players and (378) nonsmoker m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 23 publications
2
19
0
2
Order By: Relevance
“…Meo et al 24 demonstrated that, in football players the prevalence of prediabetes and T2DM was significantly low compared to control subjects The present study findings shows significant decreased prevalence of prediabetes and T2DM among cricket players compared to non-elite athlete control subjects.…”
Section: Discussionsupporting
confidence: 52%
“…Meo et al 24 demonstrated that, in football players the prevalence of prediabetes and T2DM was significantly low compared to control subjects The present study findings shows significant decreased prevalence of prediabetes and T2DM among cricket players compared to non-elite athlete control subjects.…”
Section: Discussionsupporting
confidence: 52%
“…[21][22][23] A recent study, which was conducted among elite football players found that the prevalence of prediabetes was 7.9% in the players compared to 18.78% in matched nonathlete controls. 24 The findings of this study add to the growing evidence of the alarming situation of glucose intolerance among the Saudi community.…”
Section: Discussionsupporting
confidence: 52%
“…HbA1c was measured by using a device “Clover A1c system (Inforpia, Kyunggi, Korea), an automated boronate affinity assay for the determination of the percentage of HbA1c % in the blood” [ 14 ]. The Clover A1c system is well acknowledged in the measurement of HbA1c both in clinical medicine and research.…”
Section: Subjects Ad Methodsmentioning
confidence: 99%